2005
DOI: 10.1515/cclm.2005.085
|View full text |Cite
|
Sign up to set email alerts
|

Understanding hyperlipidemia and atherosclerosis: lessons from genetically modified apoe and ldlr mice

Abstract: Hyperlipidemia is the most important risk factor for atherosclerosis, which is the major cause of cardiovascular disease. The etiology of hyperlipidemia and atherosclerosis is complex and governed by multiple interacting genes. However, mutations in two genes have been shown to be directly involved, i.e., the low-density lipoprotein receptor (LDLR) and apolipoprotein E (ApoE). Genetically modified mouse models have been instrumental in elucidating the underlying molecular mechanisms in lipid metabolism. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(96 citation statements)
references
References 75 publications
4
91
0
1
Order By: Relevance
“…Similarly, when ApoE −/− mice (8-12 months old) are fed a normal chow diet, they develop spontaneous atherosclerosis that results in the narrowing of the vessel lumen, which leads to the progressive restriction of blood flow at multiple arterial branches, including the hindlimb vessels. [40][41][42] Thus, for our study, we used 12-monthold ApoE −/− mice as cell therapy recipients because they develop chronic atherosclerosis similar to the atherosclerotic lesions observed in humans. In agreement with previous reports, we found that baseline blood flow in the nonischemic limb was better in C57 mice than in ApoE −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, when ApoE −/− mice (8-12 months old) are fed a normal chow diet, they develop spontaneous atherosclerosis that results in the narrowing of the vessel lumen, which leads to the progressive restriction of blood flow at multiple arterial branches, including the hindlimb vessels. [40][41][42] Thus, for our study, we used 12-monthold ApoE −/− mice as cell therapy recipients because they develop chronic atherosclerosis similar to the atherosclerotic lesions observed in humans. In agreement with previous reports, we found that baseline blood flow in the nonischemic limb was better in C57 mice than in ApoE −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we used the apoE −/− mouse model since its pathogenesis of atherosclerosis resembles that observed in humans and it has been widely applied in cardiovascular research 22,23) . We investigated the mechanisms of hawthorn fruit in apoE −/− mice from the two aspects of hypolipidemic and antioxidant activities.…”
Section: Hawthorn Fruit Attenuates Atherosclerosis By Improving the Hmentioning
confidence: 99%
“…Many investigators use this knockout when studying other genes involved in atherosclerosis that are not involved in lipid metabolism. 66 The major drawback to the apoE-KO model, however, is the difference in lipoprotein profiles as compared with most humans. In addition, drugs such as statins and fibrates may have disparate effects on these mice as compared with humans.…”
Section: Animal Models Of Cav and Atherosclerosismentioning
confidence: 99%
“…In addition, drugs such as statins and fibrates may have disparate effects on these mice as compared with humans. 66 The LDLR-KO mouse model compensates for the cholesterol composition; however, it does not develop complex "humanized" plaques without alteration to the diet. 66 The LDLR-KO model has shown promise in bone marrow transplantation studies, a strategy not as effective in apoE-KO because apoE from transplanted bone marrow can rescue the KO characteristics.…”
Section: Animal Models Of Cav and Atherosclerosismentioning
confidence: 99%